CELL JUNCTIONS IN OMMATIDIA OF LIMULUS - Lasansky, Arnaldo (The Rockefeller University Press, 1967)

(untitled)
The intercellular relationships in the ommatidia of the lateral eye of Limulus have been investigated. The distal process of the eccentric cell gives origin to microvilli which interdigitate with the microvilli of the retinular cells. Therefore, both types of visual cells contribute to form the rhabdom and may have an analogous photoreceptor function. Quintuple-layered junctions are found within the rhabdom at the lines of demarcation between adjoining microvilli, whether the microvilli originate from a single retinular cell, from two adjacent retinular cells, or from a retinular cell and the eccentric cell. Furthermore, quintuple-layered junctions between the eccentric cell and the tips of the microvilli of the retinular cells occur at the boundary between the distal process and the rhabdom. These findings are interpreted to indicate that the rhabdom provides an extensive electrotonic junction relating retinular cells to one another and to the eccentric cell. Quintuple-layered junctions between glial and visual cells, as well as other structural features of the ommatidial cells, are also described.